Tribute to Michael O’Rourke (1937–2024): A Collective Tribute to a Colleague, Friend and Mentor - Alberto Avolio; Barry Gow; Wilmer Nichols; Dean Winter; Christopher Hayward; David Gallagher; John Cockcroft; Audrey Adji; Junichiro Hashimoto; Charalambos Vlachopoulos (Artery Research)
Abstract A collective tribute to a colleague, friend, and mentor from those that have known him through his journey of the meanderings of the arterial pulse in health and disease; a journey that extended beyond borders and confines, with far-reaching personal and global impact. The Editorial Board of the Artery Research Journal and the Executive Committee of the Artery Society extend their due respects to Prof. Michael O’Rourke.